Pemikiran Ekosomi di Masa Umar Bin Khattab - Silalahi, Cita Ayni Putri; Putri, Dinda Shaila; Sari, Delila puspita; Nainggolan, Kristina; Kamila, Sophie Naila; Putra, M. Ramadhan (Melati Institute, 2023)
I Islam provides two important aspects in the field of economics, namely the history of economic thought and the history of economic units such as individuals, business entities and economics. Such a study of the history of economic thought in Islam will help find the sources of contemporary Islamic economic thought, on the one hand, and on the other, will allow us to gain a better understanding of the journey of Islamic economic thought over the years. Both will enrich contemporary Islamic economics and open up a wider range for its conceptualization and application, One of the most successful caliphs of Khulafâ Râshidûn in leading and prospering his people was Omar ibn Khattab. Umar bin Khatthab's government is known as a clean government supported by firm and authoritative personal characteristics so that a peaceful, prosperous and prosperous society is created. This can be proven by the economic conditions and income of the Arab community at that time which could be classified at an even economic level. They get this wealth and prosperity from the assets of the Baitul Mal Institution, Land Ownership, Zakat and Ushr.